2001
DOI: 10.1177/026988110101500310
|View full text |Cite
|
Sign up to set email alerts
|

Former chronic methylenedioxymethamphetamine (MDMA or ecstasy) users report mild depressive symptoms

Abstract: Previous work has indicated recreational use of methylenedioxymethamphetamine (MDMA or ecstasy) is associated with elevated scores on self-report measures of depression. We sought to examine the long-term effects of consumption on depression in a group of individuals who had consumed large quantities of the drug in the past, but were now leading relatively drug free lives. Respondents to this study (n = 29) had consumed an average of 1.5 ecstasy tablets in the last month, 8.4 in the last 6 months and 23.3 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
89
2
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(102 citation statements)
references
References 35 publications
9
89
2
2
Order By: Relevance
“…Considering that the forced swim test is the most widely used tool for preclinical antidepressant activity (Cryan et al, 2002), these results strengthen the claim that a neurotoxic dose of MDMA leads to increased depressive-like symptoms in animals. This converges with increasing human research that links MDMA consumption with depression (MacInnes et al, 2001;Morgan, 2000;Parrott et al, 2002). The magnitude of the MDMA effect is marginal but reliable, consistent with a report showing that MDMA users manifest mild rather than severe symptoms of depression (MacInnes et al, 2001).…”
Section: Fluoxetine and Mdma Behavioral Effectssupporting
confidence: 86%
See 2 more Smart Citations
“…Considering that the forced swim test is the most widely used tool for preclinical antidepressant activity (Cryan et al, 2002), these results strengthen the claim that a neurotoxic dose of MDMA leads to increased depressive-like symptoms in animals. This converges with increasing human research that links MDMA consumption with depression (MacInnes et al, 2001;Morgan, 2000;Parrott et al, 2002). The magnitude of the MDMA effect is marginal but reliable, consistent with a report showing that MDMA users manifest mild rather than severe symptoms of depression (MacInnes et al, 2001).…”
Section: Fluoxetine and Mdma Behavioral Effectssupporting
confidence: 86%
“…This converges with increasing human research that links MDMA consumption with depression (MacInnes et al, 2001;Morgan, 2000;Parrott et al, 2002). The magnitude of the MDMA effect is marginal but reliable, consistent with a report showing that MDMA users manifest mild rather than severe symptoms of depression (MacInnes et al, 2001).…”
Section: Fluoxetine and Mdma Behavioral Effectssupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, our finding that former ecstasy users had a high prevalence of current major depression (whereas there is no difference between current ecstasy users and lifetime non-users in the prevalence of current major depression) may be indicative of long-term adverse effects of ecstasy use. Laboratory studies have indicated that psychological well-being may be impaired and depressive symptoms reported up to 2.5 years after the cessation of heavy ecstasy use (De Win et al, 2004;Gerra et al, 2000;MacInnes et al, 2001;Thomasius et al, 2003Thomasius et al, , 2005Verheyden et al, 2003b). However, our finding that the prevalence of depression is not elevated in current ecstasy users warrants further investigation into a possible delayed effect of ecstasy on a full-spectrum depression diagnosis.…”
Section: Discussionmentioning
confidence: 58%
“…Hanson and Luciana 2004;MacInnes et al 2001;Roiser et al 2005), the SCL-90, or the related BSI or SCL-90R (i.e. Milani et al 2005;Milani et al 2004;Morgan et al 2002;Parrott et al 2001;Thomasius et al 2003).…”
Section: Discussionmentioning
confidence: 99%